IMPLEMENTASI PERDA NO. 4 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH KOTA TEGAL (STUDI PENYEDIAAN RUANG TERBUKA HIJAU) - Huda, Fajar Nur; ., Yuwanto; ., Supratiwi (Journal of Politic and Government Studies, 2013)
Regional regulation of Tegal No. 4 in 2012 about the spatial plans that the width of green open space is 30 % consist of 20% public green open space and 10% privat green open space. But in fact the land area of green open space in the city of Tegal insufficient extents mandated in the regional regulation. The purpose of the research is to know implementation of regional implementation of Tegal No. 4 in 2012 in the provision of green open space and the inhibiting factors in the implementation of regional regulation. The research proves that there are still many violations that occur in the arrangement of green open space this is due to very low level of public awareness in the provision of green open space. In addition to the lack of land and funding constraints Tegal goverment in providing green open space, socio ecconomic conditions, political and technological advancements also influence in decision making and implementationKeywords : Policy Implementation, spatial, green open space